2016
DOI: 10.1186/s12913-016-1614-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and understanding motivation among community health workers in rural health facilities in India-a mixed method study

Abstract: BackgroundMotivated human resource is the key to improve health system performance and retention of health workers. There is scanty literature on measuring motivation of health workers in India. Thus, the objective of this study was to measure and identify important aspects of health workers’ motivation in North India.MethodsA mixed method study design was adopted. Under the quantitative component, we interviewed randomly selected 62 community health workers (CHWs) in 18 sub-centres in two blocks of District A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
83
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 26 publications
(26 reference statements)
8
83
1
1
Order By: Relevance
“…Job satisfaction level of 70% among doctors at a tertiary care center is similar to our finding for doctors (71.6%) in Haryana . Another study reported around 66% median motivation levels among community health workers in Haryana . Our study found higher availability of drugs and vaccines at the public health facilities than previously published study, which evaluated the system in 2012 .…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction level of 70% among doctors at a tertiary care center is similar to our finding for doctors (71.6%) in Haryana . Another study reported around 66% median motivation levels among community health workers in Haryana . Our study found higher availability of drugs and vaccines at the public health facilities than previously published study, which evaluated the system in 2012 .…”
Section: Discussionmentioning
confidence: 99%
“…1 There is a shortage of health workers especially in developing countries including Bhutan, and task shifting to village health workers (VHWs) is one way to address the human resource shortages. 2,3 However, VHWs leaving the health systems are increasing in Bhutan. 4 The problem is not limited to that but also to growing concern about the motivation and retention of the VHWs in the health system.…”
Section: Discussionmentioning
confidence: 99%
“…16 At the family level, the shortage of manpower to look after the family and household chores 15 and having to shoulder other family responsibilities hampered them from continuing to work as VHW. 17,18 In addition, the lack of support from the spouse and other family members, 15,19 conflict with family time, 17,18 and difficulties with work-related travel 16,20 were identified as problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations